Evaluasi Program Tahsin Al-Qur’an Metode Tashili di SMP Islam Qurani Al-Bahjah Cirebon - Akhmad Hanafi; Agus Dian Alirahman; Absori Absori (Lembaga Publikasi Ilmiah Universitas Islam Bunga Bangsa Cirebon, 2024)
This research discusses the evaluation of the Quranic memorization program using the tashili method at SMP Islam Qurani (SMPIQu) Al-Bahjah Cirebon. The study is motivated by the importance of reading the Quran correctly, leading many Islamic schools to implement Quranic memorization programs. In Quranic memorization learning, a method is needed to assist students in easily reading the Quran. This memorization program aims to guide students in reading the Quran correctly and proficiently. The purpose of this research is to determine the effectiveness of the Quranic memorization program using the tashili method at SMPIQu Al-Bahjah Cirebon. The research is designed to delve into and develop understanding related to the effectiveness of the Quranic memorization program using the tashili method as the primary approach. The main focus of this research is to assess the extent to which this program can improve students' ability to read the Quran correctly and proficiently. This qualitative research employs descriptive qualitative research methods with a field research approach and the CIPP (Context, Input, Process, and Product) evaluation model. Data collection is carried out through interviews, observations, and documentation of program implementation. The collected data is then analyzed descriptively through data reduction, data presentation, and conclusions.The results of this research indicate that the Quranic memorization program is quite effective, with overall learning outcomes achieving the desired targets. Input evaluation suggests improvements in the selection of new students based on their knowledge of Quranic reading, aiming to expedite the acceptance process if conducted before admission. Process evaluation shows that the teaching schedule is well-organized as it is integrated into the teaching and learning activities. Outcome evaluation concludes that overall implementation of the Quranic memorization program at SMPIQu Al-Bahjah Cirebon has experienced a significant improvement. This research provides a valuable contribution to the understanding and evaluation of the effectiveness of Quranic memorization programs in the Islamic education environment.Keyword : Program Evaluation; Tahsin Al-Quran; Tashili Method